Prediction of Violent Extremism from Online Textual Contents - TV, Varuna (International Journal of Computer Sciences and Engineering, 2018)
Social media plays a central role in society nowadays. Extremism is also a hot topic of discussion. Violent extremist activities causes major issues. It is difficult to identify people engaging in extremist activities thorough public cyber spaces like internet cafes, institutions etc... With the help of machine learning concepts the proposed system tries to analyze the online text content and classify it in to Violent or Nonviolent content. SVM Classifier is used here. Then analyzing the user activities till now it will predict the user status, which helps to detect the extremists. The proposed system helps to detect the extremism contents and extremists as well as the extremism supporting users